Desenvolvimento profissional de professores principiantes e os movimentos para a assunção da profissão docente - Lichtenecker, Margarete Schmoel (2010)
This study is related to the Education Post - graduation Program at Education Center of Federal University of Santa Maria (UFSM)- Education Master Degree research line of Formation, knowledge and professional Development . It has been developed as a research project Dilemmas and perspectives for the educational innovation in the basic education and teacher formation and is also part of the Research Group, Researches and Interventions Educational Innovation, Educative Practices and Teacher Formation between 2008 and 2010. In order to do this, we chose to answer the following research question: which aspects are part of the professional developing process of novice teachers? The information collected and the method used to deal with this information fit in the qualitative approach. The present study involved eighteen Pedagogical coordinators (PC) and twenty-three Novice Teachers (NT), that work in Public institutions of basic education in the municipality of Santa Maria/RS, part of the State Public School System. As data collection instruments for the PC we questionnaire using a structured and mixed script with opened as well as closed questions and, for NT, a structured interview. With the intention of organize the obtained information the technique of the Collective Subject was utilized. For the analysis of all information organized we use as support some orientations from Content Analysis, proposed by L. Bardin. From this analysis and information obtained with PC and NT was possible to perceive that Basic Education Schools (BES) welcome properly the novice teachers, but neither plan nor develop specific actions for orientation of the teaching work, and also don t promote activities aiming professional development of the novice teachers, moreover, they receive the same orientations and participate of the same activities that experienced teachers do, such as pedagogical meetings, celebration events or social participations. In relation to the teaching learning, the NT point as the main criteria the need for mix theory learned in the formation courses with practice and also understand that the teaching learning is a continuous process. Besides, for the aspects that characterize the professional development of novice teachers, is clear, for both NT and PC declarations that is through continuous formation that learning happens, because according to PC the process of continuous formation provide to know new learning strategies and methodologies, showing to be interested in analyze new teaching proposals. Due to this we understand that they challenge themselves to learn, confirming that professional development and teaching learning, for these groups, are continuous and parallel. The investment in their own formation is a strong characteristic in the professional development of the groups in the study, it means, the NT known the investment in the formation is related to their professional development, whose actions, even individual, can be noticed since the choice of a profession until its ascension. When talking about being professionals, NT said the ascension occurred in different moments, mainly in the graduation, pre-professional trainingship, intership and after the stability in the profession. It is understood that professional development is for many times made of come and go, difficult situations, continuous and discontinuous moments, which may happen when assuming the profession, because as the development takes place the ascension is being consolidated.